Commercial Aspect of Agricultural Enterprising Process for Rural Economic Development - Dr William; Rohini Mahaur (International journal of economic perspectives, 2021)
“Villagers do not purchase branded products! They do not have sound purchasing power! They are illiterate! They are not aware about, what new is going in the market! etc. etc……” Before a decade, these were the common statements when discussing about rural market, but now a days these are meaningless. Many companies and management gurus has proved it myths, as Mr. C. K. Prahalad said that, “It is the bottom of the pyramid.” Though his concern was on below poverty line people, but as we knows most of such people resists in rural areas of India. Rural people have purchasing power, they are aware about branded products and they are loyal too, the need is of right positioning and right marketing strategy. This is what ITC has done for targeting rural market, and no doubt, that they are the market leader of this segment. This research paper is an approach to high light what ITC has done to become a market leader of Indian rural market. Through this paper we are focusing over myths about rural market, we are also focusing on the gap between company’s strategy and expectations of rural people from organized retailers.